Increasing the Existence of PT Telkom Indonesia in the Digital Transformation of Vocational Education in the Digitalization Era - Hidayat, Ryan Fiqih Tri; Ikaningtyas, Maharani (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Digital transformation has become a significant phenomenon in education, including vocational high school (SMK) education. In this context, PT Telkom Indonesia plays a crucial role in building a presence in the era of digital transformation in SMK education. This research aims to analyze the strategies implemented by PT Telkom Indonesia in supporting the digital transformation of SMK education. The strategies of PT Telkom Indonesia encompass the development of reliable digital infrastructure, teacher training in digital technology utilization, development of relevant content, and partnerships with SMK schools. In their implementation, PT Telkom Indonesia has created an educational environment that enables effective use of digital technology, enhancing access and quality of learning, and strengthening the existence of SMK education. Despite facing various challenges, such as unequal internet access, PT Telkom Indonesia remains committed to enhancing its strategies in supporting the digital transformation of SMK education. Through collaboration between PT Telkom Indonesia, the government, and other relevant stakeholders, it is expected that these efforts will continue to evolve and have a positive impact on building the presence of SMK education in the digital transformation era.